2018
DOI: 10.1037/adb0000330
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of female-specific cognitive behavior therapy for alcohol dependent women.

Abstract: This study compared Female-Specific Cognitive Behavioral Therapy (FS-CBT) to evidence-based, gender-neutral CBT (GN-CBT; Epstein & McCrady, 2009) for women with alcohol use disorder (AUD). Women (N = 99) with AUD, mean age 48, were randomly assigned to 12 outpatient manual-guided sessions of FS-CBT (n = 44) or GN-CBT (n = 55). Women were assessed at baseline and 3, 9 and 15 months after baseline for drinking and for specific issues common among women with AUD. A FS-CBT protocol was developed that was discrimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 60 publications
(73 reference statements)
1
37
0
1
Order By: Relevance
“… 58 The FS-CBT manual (a) highlighted two clinical themes meaningful to women, self-care and autonomy; (b) included female-specific interventions focused on coping with negative emotions and developing/enhancing women’s social network supportive of abstinence; and (c) provided women-specific examples throughout to personalize the material to each woman’s issues, such as dealing with heavy drinkers in the social network, parenting, life-stage transitions, trauma, self-esteem, and relationships. 59 In an RCT comparing FS-CBT to an evidence-based, gender-neutral CBT for AUD, Epstein and McCrady found that women in both treatment conditions were highly engaged, reported a high level of satisfaction with the treatment, significantly reduced their drinking, and improved in other areas of life functioning such as depression, anxiety, autonomy, and sociotropy. 58 There were no treatment condition effects, and the FS-CBT treatment was equally effective as the gender-neutral one.…”
Section: Aud Treatment Services For Womenmentioning
confidence: 99%
See 1 more Smart Citation
“… 58 The FS-CBT manual (a) highlighted two clinical themes meaningful to women, self-care and autonomy; (b) included female-specific interventions focused on coping with negative emotions and developing/enhancing women’s social network supportive of abstinence; and (c) provided women-specific examples throughout to personalize the material to each woman’s issues, such as dealing with heavy drinkers in the social network, parenting, life-stage transitions, trauma, self-esteem, and relationships. 59 In an RCT comparing FS-CBT to an evidence-based, gender-neutral CBT for AUD, Epstein and McCrady found that women in both treatment conditions were highly engaged, reported a high level of satisfaction with the treatment, significantly reduced their drinking, and improved in other areas of life functioning such as depression, anxiety, autonomy, and sociotropy. 58 There were no treatment condition effects, and the FS-CBT treatment was equally effective as the gender-neutral one.…”
Section: Aud Treatment Services For Womenmentioning
confidence: 99%
“…Using Network Analysis, a novel statistical approach that uses multilevel vector autoregression estimation for multiple time series data to simultaneously examine change among several hypothesized mechanisms of change, Holzhauer and colleagues compared pathways to drinking reduction among women in gender-neutral versus FS-CBT. 59 , 92 Across treatments, women changed their drinking via increased coping skills, abstinence self-efficacy, and increased autonomy. For women in FS-CBT, change in drinking also occurred through decreases in sociotropy and increases in social support for abstinence.…”
Section: Aud Treatment Services For Womenmentioning
confidence: 99%
“…At this baseline assessment, the participants met with a trained research assistant, completing additional self-report questionnaires and interviews to establish baseline measures of the outcome variables. They then were randomized to treatment condition (see parent RCT references for additional details, Epstein et al, under review; McCrady et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…For instance, issues related to interpersonal functioning, emotion and mood regulation, and self-care have been shown to be particularly prevalent and relevant among women with AUD compared to men with AUD (Walitzer & Dearing, 2006; Timko, Finney, & Moos, 2005). The data used for the current study were from two clinical trials in which the second and fifth authors developed and tested a female-specific, cognitive behavioral treatment (FS-CBT) for AUD (Epstein et al, under review). In Study 1, FS-CBT was derived from and compared to an evidence-based, gender-neutral CBT (Epstein & McCrady, 2009); the data used in the current analyses were collected from women randomized to the female-specific CBT condition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation